2000
DOI: 10.1021/ja001989s
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oligodeoxyribonucleotides with Conformationally Constrained Abasic Sugar Targets To Probe the Mechanism of Base Flipping by HhaI DNA (Cytosine C5)-methyltransferase

Abstract: X-ray crystallographic studies of HhaI DNA (cytosine-C5)-methyltransferase (M.HhaI) covalently linked to methylated 5-fluorocytosine in DNA provided the first direct evidence that the cytosine residue targeted for methylation was “flipped” out of the helix during the transfer reaction. Subsequent studies indicated that removal of the target cytosine base, i.e., introduction of an abasic site, enhanced binding of M.HhaI to DNA and that the conformation of the sugar−phosphate backbone at the abasic site in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 63 publications
3
70
0
Order By: Relevance
“…Electrophoretic mobility on native gels demonstrated that M.HhaI complexes with ODNs containing DZCyt as a replacement for the Cyt target of M.HhaI had the same 'closed' mobility in the presence of AdoMet or AdoHcy or in the absence of cofactor (Sheikhnejad et al, 1999). Identical behavior was noted for ODNs with abasic carbocyclic and furanose sugars in place of Cyt (Wang et al, 2000). An improved method for the automated synthesis of ODNs containing ZCyt (Garcı´a et al, 2001) allowed us to examine the formation of complexes between M.HhaI and ZCyt-ODN and to determine that formation of 'closed' complexes with ZCyt-ODN is also independent of cofactor (Brank et al, in preparation).…”
Section: Structural Determinants Of the Stability Of 'Closed' Complexmentioning
confidence: 86%
See 1 more Smart Citation
“…Electrophoretic mobility on native gels demonstrated that M.HhaI complexes with ODNs containing DZCyt as a replacement for the Cyt target of M.HhaI had the same 'closed' mobility in the presence of AdoMet or AdoHcy or in the absence of cofactor (Sheikhnejad et al, 1999). Identical behavior was noted for ODNs with abasic carbocyclic and furanose sugars in place of Cyt (Wang et al, 2000). An improved method for the automated synthesis of ODNs containing ZCyt (Garcı´a et al, 2001) allowed us to examine the formation of complexes between M.HhaI and ZCyt-ODN and to determine that formation of 'closed' complexes with ZCyt-ODN is also independent of cofactor (Brank et al, in preparation).…”
Section: Structural Determinants Of the Stability Of 'Closed' Complexmentioning
confidence: 86%
“…While DZCyd has the advantage of lower toxicity and mutagenic potential, it has not proven to be particularly effective at inducing a therapeutic response. With a better understanding of how mechanism based inhibitors interact with DNA methyltransferases, it should be possible to design small 'decoy' DNAs containing these inhibitors for use as therapeutics (Brank et al, in preparation;Garcı´a et al, 2001;Sheikhnejad et al, 1999;Wang et al, 2000). Dnmt1, the most abundant of the three catalytically active DNA MTase in mammalian cells (Figure 9) and the best studied, is assumed to be the major target for inhibition by Cyt analogs in DNA.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…These substrates most likely have severe backbone distortions due to steric clashes and incorrect hydrogen donor/acceptor alignment (51-53). The abasic DNA sub-strate, which most likely has the DNA backbone largely in the extrahelical conformer (54), shows the greatest biphasic behavior for loop motion. This suggests that any perturbation in DNA structure that alters the extrahelical nature of the target base will contribute to the biphasic nature of loop motion.…”
Section: Discussionmentioning
confidence: 99%
“…Many M.HhaI crystal structures provide structural insights into the mechanisms of DNA methylation and base flipping (8). Functional analysis of the WT M.HhaI has been extensive (9 -12), including K D DNA determination for a variety of DNA substrates (13,14). Many structural components of the M.HhaI mechanism have been examined by mutagenesis including Gln 237 , which positions itself into the DNA helix and interacts with the lone guanine (15), and Cys 81 , which forms a covalent bond to the target cytosine (16).…”
mentioning
confidence: 99%